Study of Understanding of MSME Actors in Balangan Regency on Trademark Rights - Muhammad Noor Ridani; Muhammad Rafly; Muhammd Haris (Sharia Journal and Education Center Publishing, 2023)
ABSTRACTTrademark is a crucial thing for producers as a hallmark of a product, especially to MSMEs as the largest contribution to the national economic generation after Covid-19, the author hopes that MSME actors have legal awareness regarding trademarks because it is a differentiator of a product from other products and focuses on one of the areas in Hulu Sungai South Kalimantan, namely Balangan Regency. This article aims to find out how public legal awareness of trademark rights and provide an understanding to MSME actors of the importance of registering a product's trademark. The writing of this article uses empirical juridical research methods, namely interviewing directly to the object of research so as to get accurate answers from the perspective of business actors so that they can provide suggestions on the problems obtained so as to produce a study that in the area especially which is the object of this research and compare it with trademark legislation, from the results of the study it can be concluded that the community of MSME actors in Balangan Regency is very interested in trademark registration but they do not really understand how the trademark registration procedure to provide legal protection to their products.Keywords: Legal Effects, Intellectual Property Rights, Trademark Rights, MSMEs. ABSTRAK Merek merupakan hal yang krusial bagi produsen sebagai ciri khas sebuah produk terutama kepada UMKM selaku sumbangsih terbesar pembangkit ekonomi nasional pasca Covid-19, penulis berharap pelaku UMKM memiliki kesadaran hukum berkenaan dengan perihal merek karena ia merupakan pembeda sebuah produk dengan produk lainnya dan berfokus ke salah satu daerah di Hulu Sungai Kalimantan Selatan yaitu Kabupaten Balangan. Artikel ini bertujuan untuk mengetahui bagaimana kesadaran hukum masyarakat terhadap hak merek dan memberikan pemahaman kepada pelaku UMKM betapa pentingnya pendaftaran merek suatu produk. Penulisan artikel ini menggunakan metode penelitian yuridis empiris, yaitu mewawancarai langsung kepada objek penelitian sehingga mendapat jawaban yang akurat dari perspektif pelaku usaha sehingga dapat memberikan saran terhadap permasalahan yang didapat sehingga menghasilkan sebuah penelitian bahwa di daerah khususnya yang menjadi objek penelitian ini dan membandingkannya dengan Perundang-undangan merek, dari hasil penelitian dapat disimpulkan bahwa masyarakat pelaku UMKM di Kabupaten Balangan sangat tertarik mengenai pendaftaran merek tetapi mereka belum terlalu memahami bagaimana prosedur pendaftaran merek untuk memberikan perlindungan hukum pada produknyaKata Kunci : Akibat Hukum, Hak Kekayaan Intelektual, Hak Merek, UMKM